2012
DOI: 10.1007/s10493-012-9647-5
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of acaricides to Raoiella indica and their selectivity for its predator, Amblyseius largoensis (Acari: Tenuipalpidae: Phytoseiidae)

Abstract: Raoiella indica Hirst (Acari: Tenuipalpidae) is considered a pest of coconut palm in Asia and the Middle East. This mite was recently introduced in the Americas, where it spread to several countries and expanded its range of hosts, causing heavy losses to coconut and banana production. The phytoseiid mite Amblyseius largoensis (Muma) is one of the predators most often encountered in coconut palms. Because the current prospects for the control of R. indica in the New World indicate the use of acaricides and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
8
1
7
Order By: Relevance
“…However, R. indica populations in the Caribbean and in areas of recent introduction are still causing damage, which suggests that additional mortality factors may be needed to effectively suppress the populations of this invasive pest, especially mortality factors affecting motile stages of R. indica. Assis et al (2013) identified acaricides that are selective for A. largoensis such as fenpyroximate and spirodiclofen, which could be used to integrate chemical and biological control strategies against R. indica. In addition, provision of alternative food sources could increase predator populations resulting in a better potential control of R. indica.…”
Section: Discussionmentioning
confidence: 99%
“…However, R. indica populations in the Caribbean and in areas of recent introduction are still causing damage, which suggests that additional mortality factors may be needed to effectively suppress the populations of this invasive pest, especially mortality factors affecting motile stages of R. indica. Assis et al (2013) identified acaricides that are selective for A. largoensis such as fenpyroximate and spirodiclofen, which could be used to integrate chemical and biological control strategies against R. indica. In addition, provision of alternative food sources could increase predator populations resulting in a better potential control of R. indica.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, não há registro, até o presente momento, de pesticidas (inseticidas) para o controle dessa espécie no Brasil. Somente, ensaios laboratoriais visando avaliação de eficiência de alguns acaricidas já foram realizados e os produtos que apresentaram Revista êxito foram abamectina, fenpiroximato, milbemectina e spirodiclofeno (Assis, Morais e Gondim, 2013).…”
Section: Introductionunclassified
“…Spirodiclofen, a tetronic acid derivative with acaricidal action, is effective against many phytophagous mite species and all developmental stages of mites, including eggs, and has a pronounced residual effect . It has been used for controlling Panonychus citri, Raoiella indica, Tetranychus urticae and Tarsonemus pallidus , P. ulmi and Aculus schlechtendali . However, the use of pesticides can hamper the effectiveness of natural enemies, interfere with their physiology, behavior, and population growth, alter the balance between natural enemies and their prey, lead to ecological backlashes, and disrupt the ecosystem services they provide .…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for controlling Panonychus citri, Raoiella indica, Tetranychus urticae and Tarsonemus pallidus , P. ulmi and Aculus schlechtendali . However, the use of pesticides can hamper the effectiveness of natural enemies, interfere with their physiology, behavior, and population growth, alter the balance between natural enemies and their prey, lead to ecological backlashes, and disrupt the ecosystem services they provide . Therefore, the conservation and augmentation of natural enemy insects in a pest management system mainly based on pesticides are important strategies to reduce the side effects of acaricides, while improving the efficiency of natural enemies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation